Fetal Growth and Well-Being Monitoring - Iin Fadhilah Utami Tammasse (Jurnal Health Sains, 2023)
Monitoring fetal well-being and growth is the key component of antenatal care. Fetal monitoring is critical to prevent fetal deaths by detecting and managing IUGR (Intrauterine Growth Restriction), congenital malformation, or genetic abnormalities of the fetus, This research uses qualitative methods with a literature review approach. Literature review is a systematic, explicit and reproducible method for identifying, evaluating and synthesizing research works and thoughts that have been produced by researchers and practitioners, Cardiotocography monitors fetal well-being by analyzing the fetal heart rate to prevent irreversible brain injury due to fetal hypoxia. CTG interpretation can help improve pregnancy outcomes by diagnosing fetal CTG abnormalities and suggesting the proper management. For example, a hypoxic fetus may exhibit abnormalities such as decreased variability of FHR onset of deceleration and no acceleration in CTG due to decreased fetal movement. In conclusion, there are several methods of monitoring fetal well-being and growth that has clinical or scientific evidence and have been used in clinical practice for years, such as cardiotocography, doppler ultrasound, fetal pulse oximetry, fetal scalp blood sampling, and fetal electrocardiogram